2017
DOI: 10.1039/c7cc04526c
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of synthetic small molecules that enhance the number of stomata: C–H functionalization chemistry for plant biology

Abstract: The increasing climate changes and global warming are leading to colossal agricultural problems such as abatement of food production and quality. As stomatal development is considered to play a key role in crop plant productivity and water-use efficiency, studying stomatal development is useful for understanding the productivity of plant systems for both natural and agricultural systems. Herein, we report the first-in-class synthetic small molecules enhancing the number of stomata in Arabidopsis thaliana that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 63 publications
0
27
0
1
Order By: Relevance
“…Thus far, four small compounds, Bikinin, Bubblin, CL1, and CL2, have been reported to modulate stomatal development (Kim et al 2012;Sakai et al 2017;Ziadi et al 2017). Bikinin was identified from a commercially available DI-VERSet compound library (ChemBridge) (De Rybel et al 2009).…”
Section: Perspectives: Synthetic Chemistry Approaches With Agriculturmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, four small compounds, Bikinin, Bubblin, CL1, and CL2, have been reported to modulate stomatal development (Kim et al 2012;Sakai et al 2017;Ziadi et al 2017). Bikinin was identified from a commercially available DI-VERSet compound library (ChemBridge) (De Rybel et al 2009).…”
Section: Perspectives: Synthetic Chemistry Approaches With Agriculturmentioning
confidence: 99%
“…This compound affects asymmetric cell division of MMCs presumably by alternating the correct localization of cell polarity factors including BASL, and, consequently, induces clustered stomata formation in Arabidopsis (Sakai et al 2017). The CL1 and CL2 were found from a specially curated small-compound chemical library (Ziadi et al 2017). Originally these compounds have an effect not only on the enhancement of stomatal development but also on plant growth where seedlings showed stunted root growth with pale green cotyledons.…”
Section: Perspectives: Synthetic Chemistry Approaches With Agriculturmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has revealed that analogues of pharmaceutical compounds can be used for other biological applications. For example, we have shown that analogues of Celecoxib, a non‐steroidal anti‐inflammatory drug, were found to enhance stomatal development in plants (Figure A) even though higher plants do not possess orthologs of the originally target gene in human . Since arylacetic acids have been regarded as privileged structures in pharmaceuticals and agrochemicals (Figure B), we envisioned that transforming the carboxyl group into other functionalities would allow for the synthesis of various analogues that would contribute drug/agrochemical discovery and chemical biology …”
Section: Figurementioning
confidence: 99%
“…[2] Therefore, these analogues would have potential to control different life phenomenont oe xpress novel bioactivity.Arecents tudy has revealed that analogues of pharmaceutical compounds can be used for other biologicala pplications.F or example, we have shown that analogueso fC elecoxib, an on-steroidal anti-inflammatory drug, were found to enhances tomatald evelopment in plants ( Figure 1A)e ven thoughh igherp lants do not possess orthologs of the originally target gene in human. [3] Since arylacetic acidsh ave been regarded as privileged structures in pharmaceuticals and agrochemicals( Figure 1B), we envisioned that transforming the carboxyl group into other functionalities would allow for the synthesis of variousa nalogues that would contributedrug/agrochemical discoveryand chemical biology. [4] Carboxylic acid moieties have long been utilized as ah andle to construct chemical bonds through the Curtius rearrangement, [5] Hunsdiecker reaction, [6] and Barton decarboxylation.…”
mentioning
confidence: 99%